1963
DOI: 10.1084/jem.118.5.845
|View full text |Cite
|
Sign up to set email alerts
|

FACTORS CONTROLLING SERUM Γ-Globulin CONCENTRATION

Abstract: The mechanisms which regulate the serum level of T-globulin (or other serum proteins) are poorly understood, although a balance between the rate of production (synthesis) and rate of removal (catabolism) must exist for the maintenance of a constant serum level. T-Globulin synthesis has been demonstrated in plasmacytes and related cells of the spleen, lymph node, bone marrow, and other tissues following antigenic stimulation (1-3), and the turnover of T-globulin has been determined by means of radioisotopically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
0
1

Year Published

1965
1965
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 160 publications
(70 citation statements)
references
References 32 publications
5
64
0
1
Order By: Relevance
“…This similarity indicated that catabolism was regulated by a property common to these classes of immunoglobulin. Other studies have shown that this is a property of the heavy polypeptide chain of the molecule (5).…”
Section: Control Of Catabolism--five Immunoglobulin Components Of MImentioning
confidence: 84%
See 4 more Smart Citations
“…This similarity indicated that catabolism was regulated by a property common to these classes of immunoglobulin. Other studies have shown that this is a property of the heavy polypeptide chain of the molecule (5).…”
Section: Control Of Catabolism--five Immunoglobulin Components Of MImentioning
confidence: 84%
“…3,1A-globulin catabolism was also unaltered by the presence of large amounts of "),lA-myeloma protein (Table II). (5,16,17) have shown that the administration of human 7S v-globulin to mice accelerates the catabolism of normal 7S v-globulin of mouse origin. The effect of human 7S v-globulin on each of the mouse 7S v-globulin components was investigated in the present work.…”
Section: E~ect Of Specific Immunoglobulinmentioning
confidence: 99%
See 3 more Smart Citations